The aesthetics of kinship : form and family in the long eighteenth century - Schlipphacke, Heidi M. (New studies in the age of Goethe., 2023)
"The Aesthetics of Kinship intervenes critically into rigidified discourses about the emergence of the nuclear family and the corresponding interior subject in the eighteenth century. By focusing on kinship constellations instead of "family plots" in seminal literary works of the period, this book presents an alternative view of the eighteenth-century literary social world and its concomitant ideologies. Whereas Enlightenment and post-Enlightenment philosophy and political theory posit the nuclear family as a microcosm for the ideal modern nation-state, literature of the period offers a far more heterogeneous image of kinship structures, one that includes members of various classes and is not defined by blood. Through a radical re-reading of the multifarious kinship structures represented in literature of the long eighteenth century, The Aesthetics of Kinship questions the inevitability of the dialectic of the Enlightenment and invokes alternative futures for conceptions of social and political life"--